Sensitivity Comparison of Pleural Fluid and Serum Neutrophil to Lymphocyte Ratio (NLR) Values in Exudative Pleural Effusion Patients - Indra Barata; Zainuddin Amir; Parluhutan Siagian; Putri C Eyanoer; Zulfikar Lubis (Perhimpunan Dokter Paru Indonesia (PDPI)/The Indonesian Society of Respirology (ISR), 2020)
Background: Delay in diagnosis and non-compliance to tuberculosis (TB) treatment will increase the risk of MDR TB. WHO recommends GeneXpert as a diagnostic tool, however, the availability is still an obstacle and this tool is not owned by many health facilities. The Neutrophil-Lymphocyte Ratio (NLR) value was thought to be used to estimate the likelihood of TB cases. This study aimed to assess the sensitivity comparison of pleural fluid and serum NLR values in patients with pleural effusion at H. Adam Malik Medan General Hospital. Methods: This was an analytical study with a diagnostic test design, by calculating the sensitivity and specificity of pleural fluid and serum NLR. The sample was calculated by comparing the absolute neutrophil count and the absolute lymphocyte count from both pleural fluid and serum. Results: The sample of this study was 78 patients. In this study, pleural fluid NLR with a cut off value of 2.2 showed a sensitivity of 74% and specificity of 28%, whereas serum NLR with a cut off value of 7.0 produced a sensitivity of 53% and specificity of 68%. Conclusion: The sensitivity of pleural fluid NLR was greater than that of serum, while the specificity of serum NLR was more superior than that of pleural fluid.